Treatment of Dementia With Bosutinib: An Open-Label Study of a Tyrosine Kinase Inhibitor. Issue 3 (June 2021) - Mahdavi, Kennedy D.; Jordan, Sheldon E.; Barrows, Hannah R.; Pravdic, Maša; Habelhah, Barshen; Evans, Natalie E.; Blades, Robin B.; Iovine, Jessica J.; Becerra, Sergio A.; Steiner, Rachel A.; Chang, Marisa; Kesari, Santosh; et al.
Abstract : Objective: The pursuit of an effective therapeutic intervention for dementia has inspired interest in the class of medications known as tyrosine kinase inhibitors such as bosutinib. Methods: Thirty-one patients with probable Alzheimer dementia or Parkinson spectrum disorder with dementia completed 12 months of bosutinib therapy and an additional 12 months of follow-up. The Clinical Dementia Rating scale (as estimated by the Quick Dementia Rating System [QDRS]) was the primary cognitive status outcome measure. Secondary outcome measures included the Repeatable Battery Assessment of Neuropsychological Status (RBANS) and the Montreal Cognitive Assessment. Cox regression methods were used to compare results with population-based estimates of cognitive decline. Results: The present article reports on cognitive outcomes obtained at 12 months for 31 participants and up to 24 months for a 16-participant subset. Safety and tolerability of bosutinib were confirmed among the study population (Mage = 73.7 years, SDage = 14 years). Bosutinib was associated with less worsening in Clinical Dementia Rating (CDR) scores (hazard ratio = −0.62, p < 0.001, 95% confidence interval [CI]: −1.02 to −0.30) and less decline in RBANS performance (hazard ratio = −3.42, p < 0.001, 95% CI: −3.59 to −3.72) during the year of treatment than population-based estimates of decline. In the 24-month follow-up, wherein 16 patients were observed after 1 year postintervention, 31.2% of participants exhibited worsened CDR levels compared with their 12-month performances. Conclusions: Results support an overall positive outcome after 1 year of bosutinib. Future studies should explore the relationship between tyrosine kinases and neurodegenerative pathology as well as related avenues of treatment.